Effect of Hemolysis on Serum Markers of Liver Function - Bhattarai, Aseem; Thapa, Ranjana; Dubey, Raju Kumar; Raut, Mithileshwar; Niraula, Apeksha; Sharma, Vijay; Tuladhar, Eans Tara (Journal of Institute of Medicine Nepal, 2024)
Introduction Samples received in the laboratory are often rejected because of visible hemolysis. Every laboratory has protocols on whether to accept or reject hemolyzed samples based on tests ordered. The objective of the study was to observe and analyze the variations seen in association with hemolyzed samples in liver function test parameters and electrolytes measurement. Methods This cross-sectional observational study was carried out in 88 laboratory samples in the Clinical Biochemistry Laboratory. Hemolysis was induced by mechanical mixing. This study compared reported values of bilirubin, protein, albumin, aminotransferases (ALT and AST), alkaline phosphatase (ALP), gamma glutamyl transpeptidase (GGT), sodium and potassium between hemolyzed and non-hemolyzed samples. Results Mean values of total bilirubin (TB) and direct bilirubin (TB), ALT, ALP, GGT and sodium (Na) were found to be significantly decreased post hemolysis (p<=0.001) with mean variances (σ2) at 0.30 (TB), 0.38 (DB), 0.56 (ALT), 0.18 (ALP), 0.01 (GGT) and 0.001 (Na). In contrast, mean values of AST (σ2= -0.9, p<0.001) and potassium (σ2 = -0.3, p<0.001) were found to be significantly elevated post hemolysis. Total protein and albumin were also found to be elevated in hemolyzed samples but the average variance was not statistically significant. Degree of hemolysis had highly varying effects in some parameters like AST and total protein, but less varying and more consistent effects on other measured parameters. Conclusion Free hemoglobin estimation should be considered before rejecting a clinical sample because of hemolysis. Mathematical equations cannot be expected to reproduce corrected values of the analytes in question because of the large variances, so these tests need to be repeated on non-hemolyzed samples for the analytes that are affected. Keywords